Review and evaluation of the role of a psychiatric pharmacist on medication management in a gender health program. Issue 12 (4th November 2022) - Wartman, Carolanne; Walroth, Todd A.; Butterfield, David; Anderson, Lindsey; Peters, Michael; Schmelz, Andrew; Ott, Carol
Abstract: Introduction: People who identify as transgender experience a significant amount of mental health concerns compared to the general population. Gender health programs offer the opportunity to provide comprehensive care for this highly stigmatized population, with the potential for psychiatric pharmacists to assist other providers and serve this need. This study aimed to evaluate the number and type of interventions made by a psychiatric pharmacist within a gender health program. Methods: A retrospective review of the electronic medical record was conducted analyzing mental health visits completed by psychiatric pharmacists within the Gender Health Program between May 1, 2020 and December 31, 2021. The primary outcome was number and type of interventions, defined as medication adjustments, laboratory monitoring, and completion of prior authorizations. Secondary outcomes included a description of medication regimens, number and type of patient education provided, and referrals to other healthcare professionals. Key subgroup analyses consisted of number of interventions based on gender identity, race identity, and insurance status. Results: There were a total of 152 appointments among 93 patients. Sixty‐one patients (66%) received at least one intervention [median (interquartile range, IQR) of 2 (2, 4)], which occurred across 81 pharmacist appointments (53%). Psychotropic medications were adjusted at 79 appointments (97%), with primarily medication initiations. Patient education was completed and documented at 102 appointments with a median (IQR) of 2 (1, 2) topics discussed per appointment. There was a statistically significant difference found between transmen and transwomen on number of interventions [31 (67%) vs 15 (45%), P  = 0.048]. Conclusion: The pharmacist in this study had the opportunity to bridge gaps in access to care to healthcare providers by initiating and managing medications, providing thorough education, and referring patients to further resources. This study affirms the accessibility and role of a psychiatric pharmacist on the interdisciplinary team caring for lesbian, gay, bisexual, transgender, queer or questioning, and more (LGBTQ+) patients.